Key tools for conducting an information audit of a higher education institution - К. A. Arzhanova; V. S. Starostin (Вестник университета)
This article focuses on the specifics of conducting a brand audit of a higher education institution (HEI) in a digital environment. The tools and peculiarities of information audit are considered and highlighted. The main advantages, differences and functionality of contemporary automatic media monitoring systems are analysed, with the focus on a number of specialised domestic and foreign closed access resources: Medialogy, Integrum, Public.ru, IQBuzz, Factiva, LexisNexis. The information on the main closed access systems is collected. Public relations and social media marketing performance evaluation indices are described. The analysis of secondary research on university reputation management is made, the results of which confirmed the hypothesis of the article about the importance of working with the media portrait of the university. It is concluded that it is necessary to conduct information audits of HEIs as part of their reputation management.